Teologi Sebagai Pencarian Makna: Rekonstruksi Teologi Islam Transformatif Berbasis Logoterapi Viktor Frankl Dalam Mengatasi Krisis Eksistensial Modern - salsabila, Chalisa; Ainiyah, Fitrotul; Nailasari, Kamelia; Siswanto, Ali Hasan (Millatuna: Jurnal Studi Islam, 2026)
The existential crisis of modern humans, marked by a disorientation of meaning, spiritual alienation, and identity fragmentation, challenges the relevance of theology in responding to humanity’s deepest needs. Modern theology tends to be trapped in normative formalism, while liberation theology and transformative Islamic theology emphasize the dimension of social praxis but often overlook existential–spiritual depth. The research gap lies in the absence of a systematic conceptual integration between transformative theological approaches and existential psychology, particularly logotherapy developed by Viktor Frankl. This article aims to reconstruct transformative Islamic theology based on the search for meaning as a response to the modern existential crisis. This study employs a qualitative- conceptual approach using the library research method, through a critical analysis of literature on modern theology, liberation theology, and Frankl’s logotherapy theory. The theoretical framework applied is a synthesis between transformative Islamic theology and existential humanistic psychology, positioning humans as meaning-seeking beings (will to meaning). The main argument of this article is that theology needs to be reoriented from merely a system of doctrines toward an existential praxis centered on the search for meaning in life, without losing its social transformative dimension. Based on this analysis, this article proposes a new conceptual framework termed Transformative Meaning-Centered Theology, which integrates spiritual, existential, and social dimensions in a holistic manner.